First record of the genus Pectapalochrus Tshernyshev, 2016 (Coleoptera, Malachiidae) from China - Tong, Junbo; Tshernyshev, Sergei E.; Liu, Haoyu; Yang, Yuxia (Biodiversity data journal)
Pectapalochrus Tshernyshev, 2016 is a small genus belonging to the tribe Apalochrini in the family Malachiidae (Coleoptera, Cleroidea), with four currently known species: P. omega (Evers, 1965) from Mongolia, P. armenus (Iablokoff-Khnzorian, 1978) from Armenia, P. pictus (Motschulsky, 1860) from Russia and P. pectinicornis (Erichson, 1840) from Russia and Mongolia.